Factors in the Design of Good Toys for Kids Aged 0-3 Years - Prachom Thangthong; Chaturong Louhapensang; Panrapee Suttiwan (My University, 2019)
Abstract The importance of ages 0-3 years of child life is considered the cornerstone of all dimensions of health for the rest of the child’s life, which is the period in which children grow rapidly and there are many changes in every aspect of development. The purpose of this study is to learn the factors that are relevant to the design of toys for kids aged 0-3 years from development, behavior of children, and the characteristics of children’s toys that are suitable for the ages, including safety. The researcher studied the guidelines for the design of kid’s toys that were appropriate to the age range. This research is a combination that uses both quantitative and qualitative methods. The results of the study after trying playing toy sets from the study of toy design factors in kids aged 0-3 from 230 samples by observing behavior from a total of 80 children, then synthesizing the data for use in the design process, and evaluating by the parents of 150 children, found that it was at a good level, with average value (x̄= 4.17, SD = 0.39). When comparing with playing toy samples from the Toy Industry Association of Thailand, it was found that there was a moderate level of satisfaction with the mean of 3.42 (x̄= 3.41, SD = 0.61), and statistically significant at 0.05 level in all aspects. In conclusion, toys for kids in the age range of 0-3 years resulting from the study of 3 factors in toy design: development and behavior, playing methods, and safety are important links between each other. Development and behavior of children are consistent with the play methods because they affect the physical development of children by age, and safety in the design of toys is able to prevent the danger that could occur to kids.
Keywords: Cornerstone; Research Design; Sports and Physical Education Research